USM SUCCESS STORY IN KNOWLEDGE TRANSFER: USING PROBIOTICS TO KEEP CHICKENS HEALTHY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, June 2015 A group of final year undergraduate students from the Universiti Sains Malaysia (USM) School of Industrial Technology (PPTI) has successfully used probiotics (friendly/good bacteria) as a replacement for antibiotics in food supplements to produce healthier chickens for human consumption.